RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI GOGO (Oriza sativa L.) DENGAN KETEBALAN TANAH MINERAL PADA LAHAN GAMBUT - Maslaita (Jurnal Pertanian Tropik, 2017)
A large area of feat soil as available across Aceh Singkil province of Aceh. The possibility of thearea for upland rice farming is a necessary tube evaluated. This study aims to evaluate the growth andyield of upland rice varieties on peat soil with different thickness of soil. The research useda randomized block design with 2 (two) factors. The first factor was rice varieties (V) were consistof (1) Local variety (Siliam varieties), (2) Situ Bagendit varieties, (3) Situ Patenggang varieties and(4) Batutegi varieties. Whereas the second-factor thickness of mineral soil applied on peat whichconsists of 5 cm, 10 cm, 15 cm, 20 cm and no mineral soil as a control. The results indicated thatvarieties of upland rice showed a significant effect on the growth and production variables such asplant height 4, 6, 8 and 10 weeks after planting, where Situ Bagendit variety was the highest amongthe varieties. Similarly, the number of tillers 4, 6, 8 and 10 weeks after planting, the highest number oftillers was found on Situ Bagendit variety, while for the highest number of grain per panicle was inBatutegi varieties. The thickness of mineral soil applicated on peat soil indicated a significant effecton the growth and production variables such as plant height 4 weeks after planting. The highestyield of upland rice was fond on Situ Bagendit variety followed by Batutegi variety, SituPatenggang variety and local variety (Siliam variety).